2016
DOI: 10.5152/eurjrheum.2015.0031
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and related factors in patients with ankylosing spondylitis

Abstract: Objective: Ankylosing spondylitis (AS) is a chronic inflammatory disease of the spine and sacroiliac joints of unknown etiology.Recent studies have reported increased oxidative stress, which is implicated in the pathogenesis of a number of diseases, in AS. The purpose of this study was to investigate oxidative stress and related factors in AS.Material and Methods: Eighty-five patients with years; 65 male/20 female] and 56 healthy subjects [36 (21-63) years; 39 male/17 female] with no known cardiovascular ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 17 publications
2
32
0
1
Order By: Relevance
“…Among all patients in the study entry, we observed significant positive correlation between IL-8 and the TBARS concentration. In our opinion, this correlation briefly describes and corresponds with the patient's condition before therapy and may suggest that disease-related factors are involved in the increased oxidative stress in AS, as suggested previously by Solmaz and Kozaci [ 16 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Among all patients in the study entry, we observed significant positive correlation between IL-8 and the TBARS concentration. In our opinion, this correlation briefly describes and corresponds with the patient's condition before therapy and may suggest that disease-related factors are involved in the increased oxidative stress in AS, as suggested previously by Solmaz and Kozaci [ 16 ].…”
Section: Discussionsupporting
confidence: 79%
“…The increased production of proinflammatory cytokines generally accompanies increased levels of oxidative stress markers [ 5 ]. Recent studies have reported an increase in oxidative stress in AS [ 15 , 16 ]. AS increases oxidant processes and decreases antioxidant capacity of the system; however, the association of AS with oxidative stress markers and cytokines remains uncertain [ 5 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A broad range of oxidation products are generated by the reaction of oxygen with unsaturated lipids (lipid peroxidation), with MDA being possibly the most mutagenic reaction product (Ayala et al ; Ying et al ; Yin et al ). Studies have found increased MDA concentrations in blood samples from symptomatic AS patients relative to the CTRL (Kozaci et al ; Solmaz et al ). The important antioxidant enzymes SOD, CAT and GSH‐PX are central in preventing damage by reducing the toxic nature of free radicals due to their capacity to scavenge superoxide radicals within cells (Kozaci et al ; Li et al ).…”
Section: Discussionmentioning
confidence: 99%
“…As seronegative spondyloarthritis (SpAS) affects predominantly the spine and the sacroiliac joints as well as the peripheral joints, especially the lower limbs [1][2][3] . The well-being of patients is greatly affected as a result of the severe damage caused by the disease in the mobility of vertebral column, resulting in physical disability 4 .…”
Section: Introductionmentioning
confidence: 99%